IMPLEMENTASI RESEARCH BASED LEARNING- RBL PADA MATA KULIAH MEDIA PEMBELAJARAN: PENELITIAN KELAS PADA MAHASISWA CALON GURU SD - Ratna Hidayah (Jurnal Bidang Pendidikan Dasar, 2018)
The content of the Learning Media courses in continuous progression PGSD based on the results of the learning media development research. RBL is relevant for implementations on the learning Media. This research was to describe the characteristics of the media learning courses PGSD and implementation of RBL on learning. This research is Classroom Research study carried out on the subjects of Media in Learning FKIP UNS Kebumen PGSD Prodi with a total of 106 students. The technique of data collection in this study; observation and interview. Data analysis includes; collection, presentation, reduction and conclusion. The results illustrate that the course aims to equip students learning media PGSD in the use and development of learning media in elementary school. The implementation of RBL on the subjects of Media Study can be executed two cycles; 1) students analyse the media learning and learning media needs, 2) students develop the learning media.